2021
DOI: 10.3390/rs13153008
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation of Key Tropospheric Parameters from ERA5 and MERRA-2 Reanalysis Products Using Radiosonde Data and GNSS Measurements

Abstract: Tropospheric delay is a major error source in the Global Navigation Satellite System (GNSS), and the weighted mean temperature (Tm) is a key parameter in precipitable water vapor (PWV) retrieval. Although reanalysis products like the National Centers for Environmental Prediction (NCEP) and the European Center for Medium-Range Weather Forecasts (ECMWF) Re-Analysis-Interim (ERA-Interim) data have been used to calculate and model the tropospheric delay, Tm, and PWV, the limitations of the temporal and spatial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…To resolve the problem that the plane position and the elevation of the NWP reanalysis dataset grid points did not coincide with those of the IGRA2 RS stations, the PWV value of four grid points around the sounding station was used to interpolate the PWV value at the RS station. In order to weaken the errors caused by the multiple interpolations, this paper first calculated the PWV value of the grid points at the same elevation as the site, and then used the Kriging interpolation method for plane interpolation [34]. Since the reanalysis dataset did not provide meteorological data at the surface, Formulas ( 5) and ( 6) were used, in this paper, to extrapolate the pressure and other parameters [33], taking the pressure calculation at station height H as an example:…”
Section: Nwp Pwv Estimation Methodsmentioning
confidence: 99%
“…To resolve the problem that the plane position and the elevation of the NWP reanalysis dataset grid points did not coincide with those of the IGRA2 RS stations, the PWV value of four grid points around the sounding station was used to interpolate the PWV value at the RS station. In order to weaken the errors caused by the multiple interpolations, this paper first calculated the PWV value of the grid points at the same elevation as the site, and then used the Kriging interpolation method for plane interpolation [34]. Since the reanalysis dataset did not provide meteorological data at the surface, Formulas ( 5) and ( 6) were used, in this paper, to extrapolate the pressure and other parameters [33], taking the pressure calculation at station height H as an example:…”
Section: Nwp Pwv Estimation Methodsmentioning
confidence: 99%
“…However, this also underlines the deficiency of accuracy in inversion ZTDs at low latitudes. Research has shown that drastic changes in temperature and water vapor could affect the accuracy of ZTD inversions using tropospheric delay models at low latitudes [45]. Temperature, precipitation, and light are important indicators of the climatic conditions of a region, indicating that different climate types may affect the inversion accuracy of tropospheric delay.…”
Section: Climate Correlation Analysis Of Errorsmentioning
confidence: 99%
“…ing tropospheric delay models at low latitudes [45]. Temperature, precipitation, and light are important indicators of the climatic conditions of a region, indicating that different climate types may affect the inversion accuracy of tropospheric delay.…”
Section: Climate Correlation Analysis Of Errorsmentioning
confidence: 99%
“…The International GNSS Service (IGS) center is operating a worldwide GNSS network with more than 400 GNSS reference stations and provides regularly a 5 min sampling ZTD (zenith total delay) tropospheric product. The accuracy of IGS ZTD estimates has been proven to be better than 5 mm [37][38][39]. To ensure the reliability of the IGS ZTD estimates, the ZTD data are screened using a quality control scheme described by Bock et al [40], and the abnormal observation data are removed.…”
Section: Pwv Retrieval From Gnssmentioning
confidence: 99%